DESIGN ANALYSIS OF EXCAVATION IN LIMESTONE QUARRIES IN REDISARI VILLAGE, ROWOKELE SUBDISTRICT, KEBUMEN DISTRICT, CENTRAL JAVA PROVINCE - Ary Sismiani; Novi Andhi Setyo Purwono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2019)
Redisari is a village located in Rowokele Sub-District, Kebumen District, Central Java. Located about 35km to the west, which is the border area between the districts of Kebumen, Banyumas and Banjarnegara. Inthis village, many limestone deposits are found, which are tertiary rocks with fan structures. With thecondition of the area consisting of these limestone deposits, the village of Redisari has the potential to be alimestone producing village. The existence of a community mine that has been running provides ideas forresearchers to participate in designing the design of excavation or mining in the first five years. From themine plan design results using the Surpac program, five designs were obtained with each volume asfollows: year 1 = 276,625 m3, year 2 = 276,825 m3, year 3 = 272,475 m3, year 4 = 278,400 m3, year 5 = 280,650 m3. The mine design at the end of year 5 is as follows: slope angle = 70, mine slope = 12%, levelheight = 10 meters and width width = 10 meters, with Safety Factor1.625. Whereas the value of safetyfactors at the end of the first year up to the end of the 5th year in a row is as follows:1.601 ; 1.589 ; 1.583 ;1.579 ; 1.577.Keywords: Mine Design, Limestone, Volume, Safety Factor of BenchABSTRAK Redisari adalah salah satu desa yang terletak di Kecamatan Rowokele Kabupaten Kebumen Jawa Tengah.Terletak sekitar 35 km ke arah barat yang merupakan wilayah perbatasan antara Kabupaten Kebumen,Banyumas dan Banjarnegara. Di desa ini baanyak dijumpai adanya endapan batugamping, yang merupakanendapan batuan tersier dengan struktur kipas. Dengan kondisi wilayah yang terdiri dari endapanbatugamping ini, maka desa Redisari berpotensi sebagai desa penghasil batugamping. Adanya tambangrakyat yang sudah berjalan memberikan ide bagi peneliti untuk berperan serta merancang desain penggalianatau penambangan pada lima tahun pertama. Dari hasil perencanaan desain tambang dengan menggunakanprogram Surpac didapatkan lima buah desain dengan masing-masing volume sebagai berikut : akhir tahunke-1 = 276,625 m3,akhir tahun ke-2 = 276,825 m3, akhir tahun ke-3 = 272,475 m3, akhir tahun ke-4 =278,400 m3, tahun ke-5 = 280,650 m3. Desain tambang pada awal tahun ke-1 adalah sebagai berikut : sudutkemiringan lereng = 70, kemiringan jalan tambang = 12%, tinggi jenjang = 10 meter dan lebar jenjang = 10 meter, dengan nilai Faktor Keamanan adalah 1.625. Sedangkan nilai Faktor Keamanan lereng padaakhir tahun ke-1 sampai dengan akhir tahun ke-5 berturut-turut adalah sebagai berikut : 1.601; 1.589; 1.583; 1.579; 1.577.Kata kunci : Desain Tambang, Batugamping, Volume, Faktor Keamanan lereng